OxLDL Is a Possible Marker for Increased Risk of Acute Coronary Syndromes - Albardan, Dima; Zrieki, Afraa; Khayat, Muhammad Imad (Latakia University Journal -Medical Sciences Series, 2022)
Objective: The aim of this study was to evaluate the usefulness of circulating oxidized low-density lipoprotein (OxLDL) as a risk marker of coronary artery disease (CAD) expressed in acute coronary syndromes (ACS) in comparison to low-density lipoprotein (LDL). Methods: A total of 78 subjects were included: 60 patients with angiographically proven acute coronary syndromes divided into acute myocardial infarction group (AMI, n=30) and unstable angina group (UA, n=30) and 18 subjects without clinical evidence of coronary artery disease served as controls. OxLDL levels were measured by sandwich enzyme-linked immunosorbent assay (ELISA). LDL levels were measured using enzymatic method. Results: Plasma levels of OxLDL were significantly higher in each disease group than in control (p<0.001). The highest OxLDL levels were associated with the presence of hypertension and/or diabetes. OxLDL levels were correlated strongly with LDL levels in controls but weakly in ACS patients. The sensitivity and specificity for diagnosing ACS were 93% and 89% respectively for OxLDL versus 77% and 72% for LDL. Conclusion: Circulating OxLDL is a better biomarker than LDL for discriminating between patients with ACS and healthy subjects. High levels of OxLDL could be a promising risk marker for coronary artery disease (CAD).